Unveiling the Role of Li+ Solvation Structures with Commercial Carbonates in the Formation of Solid Electrolyte Interphase for Lithium Metal Batteries. Issue 8 (3rd July 2021) - He, Jian; Wang, Huaping; Zhou, Qing; Qi, Shihan; Wu, Mingguang; Li, Fang; Hu, Wei; Ma, Jianmin
Abstract: Solid electrolyte interphase (SEI), determined by the components of electrolytes, can endow batteries with the ability to repress the growth of Li dendrites. Nevertheless, the mechanism of commercial carbonates on in situ‐generated SEI and the consequential effect on cycling performance is not well understood yet, although some carbonates are well used in electrolytes. In this work, quantum chemical calculations and molecular dynamics are used to reveal the formation mechanisms of SEI with carbonate‐based electrolyte additives on the atomic level. It is confirmed that the Li‐coordinated carbonate species are the leading participant of SEI formation and their impact on battery performance is clarified. Fluoroethylene carbonate (FEC) exhibits a completely different behavior from vinyl ethylene carbonate (VEC), ethylene carbonate (EC), and vinylene carbonate (VC). High reduction potential Li + ‐coordinated additives, e.g. FEC and VEC can dominate the formation of SEI by excluding propylene carbonate (PC) and LiPF6 from the decomposition, and the corresponding Li||Li symmetric cells show enhanced long‐term performance compared with those with pure PC electrolyte, while the low reduction priority additives (e.g., EC and VC) cannot form a uniform SEI by winning the competitive reaction. Abstract : High reduction potential Li + ‐coordinated additives (e.g., fluoroethylene carbonate) can dominate the formation of a solid electrolyte interphase by excluding propylene carbonate (PC) and LiPF6 from the decomposition, and the corresponding Li||Li symmetric cells show enhanced long‐term performance compared with those with pure PC electrolyte.